Przesłanki i bariery zawiązywania więzi międzyorganizacyjnych - Patrycja Klimas (Problemy Zarządzania, 2015)
This paper aims at empirical identification of the determinants and barriers to inter-organizational relationships creation in case of innovation networks. The research applied a case study method, namely analysis of a typical case study. The investigation of relationship factors was based on the purposefully chosen innovation network, Aviation Valley, as it is the one of the oldest and the biggest innovation network in Poland. The research conducted allowed us to confirm and complement the prior literature with reference to the rationale and barriers to the creation of inter-organizational relationships within innovation networks. The results of this study indicate that both the determinants and barriers to inter-organizational relationships can be described as resource-based, as they relate mainly to financial resources and the resources of knowledge and competencies. Furthermore, the results obtained allowed us also to identify some important barriers to creation of inter-organizational relationships which have not been described in the literature so far. Among these barriers there are: barrier of political and legal factors, barrier of interpersonal relationships and barrier of time-consuming nature of the process of inter-organizational relationships creation.